Vivências de lazer e de tempo livre: estudos com jovens de classe média - Oliveira, Elisa Fabris de (2015)
On a society essentially focused on work and adulthood how do middle-class youth spend their free time? And how they perceive and give significance to experiences that happen on these social circles arenas? This dissertation, developed based on two studies, had as main goal answer these questions. The intention was to analyze the leisure and free time of middle-class youth to understand better the youth in itself and its social realities. The research‘s first stage has as instrument a questionnaire with structured questions that investigated socio-demographic issues in a quantitative way; access to entertainment and technological goods; ways of experiencing free time; personal issues; and family, school and community context. 270 high school students from Vitória, Espírito Santo, with age varying from 14 to 19, answered the questionnaire. With the results – obtained with SPSS support - , was possible to ascertain the importance that media products has on the participants free time spending habits; the association between gender and chosen activities during free time; high averages on Self-efficiency, Self-esteem and Future Perspectives; and the youth‘s good perception about the three analyzed contexts, especially the family context. The research‘s second stage adhered to identifying and understanding the social representations of leisure and youth free time; assuming as theoretical contributions the Social Representations Theory and the Central Core Theory. This stage, called Study 2, was developed according to a quanti-qualitative methodology through free association tasks and four focus groups. The same high-school students from Study 1 and other 21 participants were used as investigation samples; also with age varying from 14 to 17. The results obtained with this data, partially analyzed using openEvoc and partially using the content analysis technique, revealed that free time is perceived and lived by young primarily through typical daily activities that are usually viewed as not optional. Leisure, on the other hand, was perceived as a phenomenon that brings pleasure, fun and well-being, and that is essentially experienced from socializing and sports. In conclusion, we observed the social character of leisure and free time of middle-class young people; being anchored in core values and standards of our capitalist society, and recognized as secondary importance activities when compared to study, productivity and the quest for professional success.